A angústia diante da morte: um estudo à luz da psicanálise freudiana - Lima, Bruna Souza de (Universidade Federal de São Carlos, 2026)
This research aims to investigate and understand anxiety in the face of death in light of Freudian psychoanalytic theory, especially in conjunction with the formulations of the second theory of anxiety. It also seeks to understand how cultural structures mobilize to attribute meaning and manage this type of anxiety. To carry out the investigation, a historical overview of the subject's relationship with death in the West was constructed, as well as an analysis of the development of the notion of anxiety in the face of death in Freud's work. Next, the main metapsychological concepts related to it were explored in depth, namely: anxiety, helplessness, castration anxiety, anxiety in the face of the superego, and the constitution of the superego. The relationship between religion and death is also discussed, examining the origin of religious conceptions based on the experience of helplessness and nostalgia for the father figure, and the relationship between science and anxiety in the face of death, exploring the articulation between the death drive and the destruction drive and the role of science in enhancing the destruction of others through the development of military technologies. It is proposed that anxiety in the face of death is not reduced to an instinctive fear of biological extinction, but articulates psychic dimensions related to helplessness, loss of protection, and the instances that sustain the subject.
Anxiety in the face of death: a study in light of Freudian psychoanalysis
Keywords: Morte; Angústia da morte; Desamparo; Supereu; Religião; Ciência; CIENCIAS HUMANAS::PSICOLOGIA; 3. Saúde e Bem-Estar